ATMP Environmental Exposure Assessment in European Healthcare Settings: A Systematic Review of the Literature - Damerval, Margaux; Fagnoni-Legat, Christine; Louvrier, Aurélien; Fischer, Sarah; Limat, Samuel; Clairet, Anne-Laure; Nerich, Virginie; Madelaine, Isabelle; Kroemer, Marie (Frontiers in Medicine, 2021)
Since 2007, a new class of biologic products for human use called “Advanced Therapy Medicinal Products (ATMP)” have been legally integrated in the European Medical Agency. They consist of recombinant nucleic acid, engineered cells, cells or tissues. In the United States, ATMP also fall under the regulatory framework of biological products and the term “cell and gene therapy product” is used in legislative and regulatory documents. Potential clinical applications are broad, particularly in the field of cancer, inherited genetic disease and regenerative medicine. Indeed, the benefit conferred by CD19 Chimeric Antigen Receptor T cells led to the first engineered cell therapy products to be FDA (Food and Drug Administration) approved in 2017. Gene therapy products to treat orphan diseases are also extensively developed with many clinical trials ongoing in the world. Nevertheless, the use of these therapeutic products is complex and requires careful considerations in terms of regulatory and hospital setting requirements like storage, handling, administration, and disposal which justify the implementation of a secured medication circuit. Through this systematic review of the literature, the authors wanted to compile data on the assessment of environmental exposure related to the use of ATMP in healthcare setting to secure their medication circuit. A literature search was conducted on PubMed and Web of Science, and 32 publications dealing with environmental exposure assessment and ATMP were selected. In addition, marketed ATMP were identified and data regarding environmental concerns were extracted from product information sections from European Public Assessment Reports (EPAR). Environmental contamination assessments were mainly addressed in reviews rather than in original articles related to the use of ATMP. Most of the product information sections from EPAR suggested precautions rather than requirements when dealing with environmental consideration following ATMP handling. Nevertheless, these precautions usually remain elusive especially concerning waste disposal and the detection of biological material on work surfaces, and mainly relate to genetically modified organisms (GMO) over non-GMO cellular products. Pharmaceutical oversight and adherence to good preparation practices and good clinical practices are essential to ensure the safe use in term of environmental concern of these new therapeutic products in healthcare setting.